How health care providers should address vaccine hesitancy in the clinical setting: Evidence for presumptive language in making a strong recommendation. Issue 9 (1st September 2020) - Jacobson, Robert M.; St. Sauver, Jennifer L.; Griffin, Joan M.; MacLaughlin, Kathy L.; Finney Rutten, Lila J.
ABSTRACT: Vaccine hesitancy occurs throughout the world and can result in poor vaccine uptake and vaccine-preventable disease-outbreaks. Vaccine hesitancy dates back to the days of Edward Jenner and the smallpox vaccine. It persists despite the preponderance of evidence supporting vaccine safety and effectiveness. Studies show even among parents of well-vaccinated children that 15–35% of those parents are vaccine-hesitant. Studies have failed to show the efficacy of educational interventions, and, indeed, a number of studies of educational interventions show a contrarian effect leaving the vaccine-hesitant more entrenched in their views. Still dozens of studies support health care provider recommendation as a major factor in achieving high rates of vaccine uptake. Furthermore, studies find those recommendations perceived as stronger are more effective than those perceived as weaker. What makes for a stronger recommendation? Several observational studies indicate that presumptive, announcement language as contrasted with participatory, conversational language makes for a stronger more effective recommendation. Several trials now demonstrate that health care providers and practices can implement this language and obtain higher vaccination uptake. The authors recommend the practice be adopted as a routine practice in the clinical setting for all vaccinations